2016
DOI: 10.7819/rbgn.v18i62.2743
|View full text |Cite
|
Sign up to set email alerts
|

Actor networks in specialized accounting inspection: an analysis in the light of the Actor-Network Theory

Abstract: Purpose -This study investigated the configuration of human and non-human actor networks that are formed in the process of specialized accounting inspection from the Actor-Network Theory perspective.Design/methodology/approach -The population of the survey comprised 593 accounting experts registered in Expert Associations from the Brazilian states of Minas Gerais, Paraná, Rio de Janeiro, Rio Grande do Sul and São Paulo, and the sample is made up of 102 valid questionnaires. Five judges and five accounting expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Based on this research, he concluded that establishing a network in the field of professional accounting inspection depends on a large number of translations between agents. Because these translations have an impact on the execution of activities and the stability of relations [3]. The purpose of Rutherford BA is to analyze accounting research projects related to the ambiguity of accounting narratives, focusing on the early literature on the readability of accounting narratives.…”
Section: Related Workmentioning
confidence: 99%
“…Based on this research, he concluded that establishing a network in the field of professional accounting inspection depends on a large number of translations between agents. Because these translations have an impact on the execution of activities and the stability of relations [3]. The purpose of Rutherford BA is to analyze accounting research projects related to the ambiguity of accounting narratives, focusing on the early literature on the readability of accounting narratives.…”
Section: Related Workmentioning
confidence: 99%
“…e protection method refers to the fact that the data information is uploaded to the cloud computing technology platform so that the relevant information resources are centrally stored in a database so that the data information can be protected, and the system will automatically redistribute according to the needs when using. But it is also because the virtual accounting information system composed of cloud computing technology is based on the network; that is, to use this service platform, it is necessary to transfer the data information resources to a third-party platform that cannot be seen, which will also increase the risk of information security [12]. erefore, we should pay attention to the use of cloud computing technology to truly serve information security.…”
Section: Information Securitymentioning
confidence: 99%